KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN RASIO KEUANGAN DAN KONSEP ECONOMIC VALUE ADDED (EVA) (Studi Kasus pada PT. Pertamina Periode 2012-2014) - Riberu, Dorotea Noesman; Sandari, Tries Ellia (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTState-Owned Enterprise is a state-owned company. Weak control and control that causes a decline in the performance of state-owned companies. The purpose of this study is to determine the company's financial performance using financial ratio analysis and EVA concepts. The method used in this research is descriptive quantitative approach, because it only describes the company's financial condition through quantitative calculations of some financial ratios and EVA concepts. The object of this research is PT Pertamina which is listed on the Indonesia Stock Exchange. Performance of PT. Pertamina has a very poor performance, because the liquidity ratio has not reached maximum results. The solvency ratio must improve DTAR derived from loans or debt. Activity ratio is only inventory turnover which shows quite good, profitability ratios increase sales so that the resulting profit increases. The results of the analysis of financial performance using EVA, that the financial performance of PT. Pertamina experienced a decline in 2012 and 2013, then experienced an increase in 2014. It shows that the company's financial performance using EVA is considered not good, because it has not managed to achieve a positive value (EVA> 0) in 2012 and 2013. But in 2014, EVA is considered quite good, because it has managed to achieve a positive value (EVA> 0), so it can be concluded that the company is only able to produce economic added value in 2014. This means that in 2014 the company can meet the level of returns expected by investors, both creditors or shareholders. Keywords: Financial Performance. Financial Ratios, EVA